Introducing Religious Moderation through Local Wisdom for Early Childhood - Lestari, Dwi Puji; Nopiana, Nopiana (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2024)
Various cases of suicide bombings in several regions in Indonesia, terrorism movements, the development of thought dynamics that cause various differences, and various issues of intolerant practices that occur at the kindergarten/PAUD level. Conflicts arising from diversity in Indonesia pose a significant challenge to the country’s ability to maintain unity. The purpose of this study is to explain the strategy for introducing religious moderation through local wisdom in early childhood. The research methodology employs a qualitative literature review method. We gather documentation data by searching through a variety of books and articles using keywords such as religious moderation, early childhood, and local wisdom. The data analysis process employs content analysis, which involves scrutinizing data from a variety of sources and drawing conclusions from the findings. The study’s findings demonstrate that local wisdom can introduce religious moderation, as it closely aligns with the child’s surroundings, making religious moderation an integral part of children’s lives. Family, school, and community education can facilitate the integration of moderation and local wisdom. This study offers a fresh perspective on the strategy of introducing religious moderation to early childhood by integrating local wisdom values to form an inclusive, tolerant, and open character towards diversity.